Sustainable Organocatalytic Processes to Access Alkyl SuFEx Click Hubs and Tetrasubstituted Carbon Centers: Potential Libraries for Multidisciplinary Applications - Kim, Woo Hee; Park, Jin Hyun; Lee, Sun Bu; Israr, Muhammad; Koo, Byeong Jun; Kim, Soo Bok; Kim, Soyeon; Bae, Han Yong (Synlett, 2023)
In this Account, we provide an overview of our recent achievements on sustainable organocatalysis. Our group has unveiled the effectiveness of specific organocatalysts under various environmentally benign conditions. We have found that N-heterocyclic carbene and phosphazene superbases exhibit favorable performances in bulk aqueous reaction environments. In addition, the use of organic superacid catalysts results in synergistic effects when hydrogen-bond donor catalysts are assembled in aqueous media. Moreover, we discovered that a neutral organic salt precatalyst can generate a potent silylium Lewis acid catalyst in situ, specifically under solvent-free conditions. These innovative, sustainable organocatalytic processes have successfully facilitated the conversion of raw starting materials into valuable compounds, including sulfur(VI) fluoride exchange (SuFEx) click hubs and tetrasubstituted carbon centers incorporating heteroatoms.1 Introduction2 Water-Accelerated N-Heterocyclic Carbene (NHC) Catalysis for β-Aminosulfonyl Fluorides3 Water-Accelerated Phosphazene Superbase Catalysis for β-Sulfidosulfonyl Fluorides and γ-Geminal Dithioester-Incorporated Sulfonyl Fluorides4 Water-Accelerated Synergistic Superacid Catalysis for α-Tertiary Amines5 Solvent-, Metal-, and Purification-Free PPM (parts per million) Neutral Organic Salt Catalysis for Tertiary Cyanohydrin Derivatives6 Conclusion
Keywords: organocatalysis; sustainable process; on-water; solvent-free; sulfur(VI) fluoride exchange (SuFEx); tetrasubstituted carbon centers